Base de conhecimento para o ensino nas licenciaturas em matemática: uma análise das concepções dos professores formadores sobre suas práticas pedagógicas - Zero, Beatriz de Macêdo (Universidade Federal de São Carlos, 2020)
This research aims to: analyze conceptions from teacher educators in Mathematics on their pedagogical practices and relate them to the elements of knowledge base for the teaching proposed by Shulman (1987) – such concepts were explored through the narratives that teachers brought about their practices; survey which instruments and methodological strategies are composed as teacher educators’ pedagogical practices and to verify if teachers think about the possibilities of construction of the elements of the knowledge base for the initial training of new teachers. It is a qualitative research carried out through a field study. Teachers with a degree in Mathematics from three Brazilian public institutions were invited to participate in an online questionnaire related to their education, professional experiences, and practices (pedagogical practices). Subsequently, a sample was selected and interviewed for a better understanding of the documents' discourse and deepening of the questionnaire. The speeches selected in the interviews about pedagogical practices could be articulated to the elements of the knowledge base for teaching and to the processes of reasoning and pedagogical action. The data show that teachers present conceptions about what they do and highlight possibilities of actions on various problems that can be overcome through the elements of the base.
The knowledge base of teaching in pre-service mathematical education: an analysis of the concepts of teacher educators about their pedagogical practices
Keywords: Base de conhecimento para o ensino; Prática pedagógica; Professores formadores da licenciatura em Matemática; Knowledge base for teaching; Pedagogical practice; Teachers with a degree in Mathematics; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM::METODOS E TECNICAS DE ENSINO